TRADISI MINUM MINUMAN MOKE PADA MASYARAKAT DESA MBOTUTENDA KECAMATAN ENDE KABUPATEN ENDE - khusnul Khotimah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Moke is one of the traditional alcoholic and natural drinks made from palm trees and the manufacturing process is through distillation. The word moke comes from the Ende language which means liquor. The people in Mbotutenda Village are inseparable from the habit of consuming moke even though the alcohol content is very high. This is because according to custom and tradition, moke is a drink that cannot be separated from any traditional celebrations or ceremonies such as traditional rituals at weddings or what is commonly called inter-belis and mourning events. Moke is also symbolized as a drink of brotherhood, and a means of unity in social life. This study aims to find out how the moke drinking tradition in Mbotutenda Village is This type of research used by researchers is to use a type of qualitative research. This definition clearly illustrates that qualitative research prioritizes natural settings, so that the results can be used to interpret phenomena, and the methods usually used are interviews, observations, and utilization of documents. Moke is a typical drink from the island of Flores which is made from palm sugar. This drink has many names such as sopi, dewe, and moke, but the name that is most familiar and characteristic of the island of Flores is moke. Moke is a symbol of custom, brotherhood and association for the people of Flores. Moke drink in the culture of the people of Mbotutenda Village has become a hereditary tradition in traditional ceremonies. Continuing this tradition, on the one hand, is felt as a necessity for the people of the mbotutenda village, but on the other hand, there are things that are felt to be inconsistent with the general ethics of the Indonesian people. The ethical violation is when someone has to consume moke to get drunk. as a mandatory drink at every event or traditional ritual of the Mbotutenda Village community, it will be consumed by all levels of society, both male and female, young or old